Touch in Irish performance art: Haptic encounters in Becoming Beloved (1995) and The Touching Contract (2016) - Antosik-Parsons, Kate (My University, 2020)
Over the last 50 years, Irish feminists have campaigned for women’s sexual health and reproductive rights including access to contraception, legal abortion and choice in maternity care and childbirth. Recent cases like Ms. Y (2014); P.P. v HSE (2014); and Ms. B (2016); invite close scrutiny of the power dynamics relating to women’s reproductive bodies in Ireland. This essay examines the haptic encounters in Becoming Beloved (1995) and The Touching Contract (2016), two performance-based artworks located in Dublin maternity hospitals. Both artworks centred the body as a site of production to interrogate these power dynamics by emphasizing autonomy and consent while engaging with site-specific locations. This essay charts the management of childbearing bodies in Ireland, looking specifically at issues concerning reproductive and sexual health, information, and consent. It details how Irish performance art has responded to the political, social and cultural climate of restrictions on women’s bodies. Becoming Beloved and The Touching Contract both employed haptic encounters, multisensory perceptions composed of tactile, kinaesthetic and proprioceptive sensations that extended beyond a visual aesthetic. These haptic encounters contributed to a dimension of viewer engagement, integral in performance art to activate meaning. This article examines how these two artworks utilized haptic encounters to produce a situated, corporeal knowledge that critiqued the authority wielded over reproductive bodies by political, religious and medical establishments in Ireland.
PUBLISHED
Keywords: Irish art; Embodiment; Feminism; Haptic; Performance art; Reproductive rights